Door - Lauterbach, Ann 1942- (Penguin Books, 2023)
"In Ann Lauterbach's eleventh collection, the image of a Door recurs across several poems, as she considers the perpetual dialogue between what is open and what is shut for each of us. The Door is a threshold between the inner landscape of memory, thought, imagination and dream and the outer so-called real world, which increasingly comes to us through technology's lens, displacing and distorting our sense of intimacy, presence and relation. What is near, and what is far away? She asks about the efficacy of language itself, when confronted by the urgent uncertainties of contemporary experience"--
Keywords: poetry; Poetry; Poésie